Chemical and Electrochemical studies on the corrosion of mild-steel, copper and zinc in 0. 5 M H2SO4 solution in presence of Azithromycin as effective corrosion inhibitor (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
Azithromycin has been tested as inhibitor for steel, copper and zinc corrosion in 0.5 M H2SO4 was studied using potentiodynamic polarization and electrochemical impedance spectroscopy.Â  The results showed that the inhibition efficiency increased with increasing the concentration of Azithromycin. The adsorption characteristics of Azithromycin in presence of steel, copper and zinc metals were studied and the dataÂ  found to fit the Kinetic-Thermodynamic model. IR spectroscopy of the corrosion product with the inhibitor confirmed the formation of metal ion inhibitor complex.